A fábrica Codorna: conflitos, práticas e experiências na (re)construção de memórias - 1997-2008 - Taveira, Luciene Peixoto (2009)
This dissertation is set in the field of Social History of the Pontifical Catholic University of São Paulo. It comprises an investigation on the experiences and justifications of the members of the Historical Heritage Council of the city of Itajubá in the years of 1997 and 1998 during the attempts to register the old building of Codorna Textile Factory as Historical Heritage. It also comprehends a reflection regarding the memories of the old factory workers based on their life experiences. The goal of this study is to reflect on the experience of several subjects in the construction of their memories and in the meanings surrounding the factory, which operated between 1914 and 1966 in the city of Itajubá, Minas Gerais